Analisis Penyusunan Anggaran Dalam Kaitannya Dengan Rencana Akuntansi Pertanggungjawaban Manajemen Pada Pdam Tirta Pakuan Kota Bogor - Setiawan, Hendra; Hastoni, Hastoni; Ginanjar, Agung (Jurnal Ilmiah Ranggagading (JIR), 2011)
Process budgeting arrangement is negotiation event between the manager responsibility centre with the superior to decided what will be do by the manager and how. The result from this negotiation is a statement that has been legalize about profit and expenses that has been expect along budgeting year to every responsibility centre and to the organization in general. In general, a company was separate into parts that smaller who been given several kinds of responsibility. This parts was called division, department, business unit etc. every parts who responsibility to every several managerial task. An organization leader has to make sure that individual in every department work to achieve goal that has been decided by the top management. Responsibility accounting is a concept and a device that used by the management in assess individual and department to make achieve several goal. The motive of this research is to analysis budgeting arrangement that doing by the company in correlation with management responsibility accounting. Analysis been doing to see the method of budgeting arrangement that company doing has appropriate with the order who match so it can be responsible by the manager to every incorrect thatâs happen between realization and budgeting who has been decided. The research that writer do is in PDAM Tirta Pakuan Kota Bogor. The company works in given serve in drinking water. The result from the research show that PDAM Tirta Pakuan Kota Bogor has arrange the budget with well and it appropriate with the order who match, this thing saw from the result of the compare between budget and realization who has difference assess not very far. Beside that, PDAM Tirta Pakuan Kota Bogor also has used responsibility accounting very well, its can see from the assign of power and responsible that very good and direct also its doesnât had one unit who have double duty and responsible.